Dependence of Groundwater Quality on Rainfall - Joseph, Jesiamma; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
Like weather forecast, quality forecast is also of vital importance for the management of groundwater resources. An attempt has been made to relate quality variation with rainfall by correlation analysis. Linear relationship model has been developed using the rainfall and chemical characteristics observed since 2001 in different wells of Calicut town area. Mixed trend of variation is found.